Oxidative stress, superoxide production, and apoptosis of neutrophils in dogs with chronic kidney disease - Silva, Adriana Carolina Rodrigues Almeida [UNESP]; de Almeida, Breno Fernando Martins [UNESP]; Soeiro, Carolina Soares [UNESP]; Ferreira, Wagner Luis [UNESP]; Lima, Valéria Marçal Felix de [UNESP]; Ciarlini, Paulo Cesar [UNESP] (My University, 2013)
Oxidative stress is a key component in the immunosuppression of chronic kidney disease (CKD), and neutrophil function may be impaired by oxidative stress. To test the hypothesis that in uremic dogs with CKD, oxidative stress is increased and neutrophils become less viable and functional, 18 adult dogs with CKD were compared with 15 healthy adult dogs. Blood count and urinalysis were done, and the serum biochemical profile and plasma lipid peroxidation (measurement of thiobarbituric acid reactive substances) were determined with the use of commercial reagents. Plasma total antioxidant capacity (TAC) was measured with a spectrophotometer and commercial reagents, superoxide production with a hydroethidine probe, and the viability and apoptosis of neutrophils with capillary flow cytometry and the annexin V-PE system. The plasma concentrations of cholesterol (P = 0.0415), creatinine (P < 0.0001), and urea (P < 0.0001) were significantly greater in the uremic dogs than in the control dogs. The hematocrit (P = 0.0004), urine specific gravity (P = 0.015), and plasma lipid peroxidation (P < 0.0001) were significantly lower in the dogs that were in late stages of CKD than in the control group. Compared with those isolated from the control group, neutrophils isolated from the CKD group showed a higher rate of spontaneous (0.10 ± 0.05 versus 0.49 ± 0.09; P = 0.0033; median ± standard error of mean) and camptothecin-induced (18.53 ± 4.06 versus 44.67 ± 4.85; P = 0.0066) apoptosis and lower levels of superoxide production in the presence (1278.8 ± 372.8 versus 75.65 ± 86.6; P = 0.0022) and absence (135.29 ± 51.74 versus 41.29 ± 8.38; P = 0.0138) of phorbol-12-myristate-13-acetate stimulation. Thus, oxidative stress and acceleration of apoptosis occurs in dogs with CKD, the apoptosis diminishing the number of viable neutrophils and neutrophil superoxide production.
Keywords: camptothecin; cholesterol; creatinine; phorbol 12 acetate 13 myristate; superoxide; urea; animal cell; animal experiment; apoptosis; cell viability; chronic kidney disease; controlled study; dog; flow cytometry; hematocrit; leukocyte differential count; lipid peroxidation; neutrophil; nonhuman; oxidative stress; spectrophotometry; uremia